Asuhan Kebidanan Pada Balita Dengan Masalah Diare Di Praktek Mandiri Bidan Risanna Wilayah Kerja Puskesmas Laboy Jaya Tahun 2023 - Br ritonga, Afrilia Rahma; Apriyanti, Fitri; Parmin, Joria (Evidence Midwifery Journal, 2024)
Diarrhea is still a global problem with high levels of morbidity and mortality in various countries, especially in developing countries, and is also one of the main causes of high morbidity and mortality rates for children under five in the world, especially for children aged 1 to 4 years. The role of midwives is very important in providing midwifery care to toddlers with diarrhea problems. Obtaining evidence based in addition to Varney’s 7 steps regarding 5 types of diarrhea as a reference for handling toddlers with diarrhea and obtaining treatment for diarrhea. This research aims to determine midwifery care for toddlers with diarrhea problems at the Risanna Midwife Independent Practice in the Laboy Jaya Health Center Work Area in 2023. The type of research used in the case study is descriptive research. The subject of this case study is a toddler with diarrhea, namely An.F. The results of this research were midwifery care for toddlers aged 4 years who experienced diarrhea problems at PMB Risanna, Laboy Jaya Community Health Center Working Area in 2023, by providing ORS, zinc tablets, nutritious food in small but frequent portions (eggs, vegetables, temped and tofu) and health education on how to prevent diarrhea in toddlers. The assessment was carried out using SOAP and carried out in 3 visits with the result that An.F recovered from diarrhea. It is hoped that mothers of toddlers will prevent dehydration in toddlers who experience diarrhea, such as giving ORS from household kitchen ingredients, namely a mixture of salt and sugar as initial management for toddlers suffering from diarrhea